Influence of Social Networking Usage towards Youth Involvement, Attitude and Confidence in Voting - Michael W. Arabani; April Boy C. Bayon-on; Josef Mari M. Ocampo; Ronel Geraldizo Dagohoy (Journal of Government and Political Issues, 2022)
The youth’s involvement with politics, attitudes, and confidence in their decision-making during electoral events have been considered as one of the elements for a healthy democratic country. Thus, this study assessed the influence of social networking usage on youth involvement in politics, attitudes towards voting, and confidence in voting decisions. This study also investigated what domain of social networking site usage best influences the youth involvement with politics, attitude toward voting, and confidence in their voting decisions. The study is quantitative research utilizing the descriptive-correlational research design. This study was conducted on the 348 students of Davao del Norte State College, which choose by stratified random sampling. The study revealed that social networking site usage was described as high. While the youth involvement, attitude, and confidence in voting were described as very high. Moreover, social networking site usage and youth involvement, attitude, and confidence in voting reveal a moderate positive relationship. The perceived usefulness is the domain of social networking site usage that significantly influences the youth involvement, attitude, and confidence in voting. The findings of this study serve as information on how to use social networking sites in dealing with young voters to improve their political perceptions and beliefs, their electoral behavior, and confidence in their voting decision.